Alnus hirsuta (Spach) Rupr. Attenuates Airway Inflammation and Mucus Overproduction in a Murine Model of Ovalbumin-Challenged Asthma - Lee, Ba-Wool; Ha, Ji-Hye; Ji, Yeongseon; Jeong, Seong-Hun; Kim, Ju-Hong; Lee, Jihye; Park, Ji-Young; Kwon, Hyung-Jun; Jung, Kyungsook; Kim, Jong-Choon; Ryu, Young-Bae; Lee, In-Chul (Frontiers in Pharmacology, 2021)
Alnus hirsuta (Spach) Rupr. (AH), a member of the Betulaceae family, is widely used to obtain medicinal compounds in the Republic of Korea and China to treat hemorrhage, diarrhea and alcoholism. In this study, we investigated the protective effects of a methanolic extract of AH branches against airway inflammation and mucus production in tumor necrosis factor (TNF)-α-stimulated NCI-H292 cells and in an ovalbumin (OVA)-challenged allergic asthma mouse model. We injected OVA (40 μg) with 2 mg of aluminum hydroxide on days 0 and 14 to induce allergic airway inflammation in female BALB/c mice. The mice were challenged with 1% OVA from days 21 to 23. The AH (50 and 100 mg/kg/day; 2% DMSO) and dexamethasone (positive control; 3 mg/kg/day) were administered from days 18 to 23. The AH effectively attenuated airway hyperresponsiveness and reduced levels of T helper type 2 (Th2) cytokines and eotaxins, the number of inflammatory cells in bronchoalveolar lavage fluid, and immunoglobulin E levels in serum of OVA-challenged mice. In histology, AH treatment significantly inhibited airway inflammation and mucus production in OVA-challenged mice. AH treatment also downregulated the phosphorylation of I kappa B-alpha, p65 nuclear factor-kappa B (p65NF-κB), and mitogen-activated protein kinases with suppression of mucin 5AC (MUC5AC) in lung tissue. Moreover, the AH treatment decreased pro-inflammatory cytokines and Th2 cytokine levels and MUC5AC expression, as well as inhibited the phosphorylation of p65NF-κB in TNF-α-stimulated NCI-H292 cells. These results indicate that AH might represent a useful therapeutic agent for the treatment of allergic asthma.